The Effect of Applying the Problem Based Learning Model to Improve the Ability to Analyze Intrinsic Elements of Short Stories - Wandi; Iis Ristiani (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to determine the effect of applying the Problem-Based Learning model on improving the ability to analyze the intrinsic elements of short stories. This study uses a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The study was conducted in the odd semester of 2025/2026 at SMPN 5 Campaka. The population of this study was ninth-grade students who participated in learning using problem-based learning. The research sample consisted of two classes: the experimental class, which received treatment using the Problem-Based Learning model, and the control class, which received conventional learning. Data were collected through pre- and post-tests on the ability to analyze the intrinsic elements of short stories. Data were analyzed using descriptive statistics and parametric inferential statistics, namely the t-test. The results of the study indicate that the application of the Problem-Based Learning model has a significant impact on improving students' abilities to analyze the intrinsic elements of short stories. Students who learned using the Problem-Based Learning model showed a higher increase in scores compared to students who learned conventionally. Thus, the Problem-Based Learning model is effectively used in literature learning to develop students' critical and analytical thinking skills.